2017
DOI: 10.1055/s-0037-1598655
|View full text |Cite|
|
Sign up to set email alerts
|

Absorbable Implant to Treat Nasal Valve Collapse

Abstract: To evaluate the safety and effectiveness of an absorbable implant for lateral cartilage support in subjects with nasal valve collapse (NVC) with 12 months follow-up. Thirty subjects with Nasal Obstruction Symptom Evaluation (NOSE) score ≥ 55 and isolated NVC were treated; 14 cases were performed in an operating suite under general anesthesia and 16 cases were performed in a clinic-based setting under local anesthesia. The implant, a polylactic acid copolymer, was placed with a delivery tool within the nasal wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 20 publications
3
39
1
1
Order By: Relevance
“…Their analysis required pooling of data samples with different lengths of follow‐up and different intervals of reporting, prohibiting drawing definitive conclusions regarding the trend of NOSE scores longitudinally. For example, San Nicolo et al performed polylactic acid copolymer implants within the nasal wall for lateral cartilage support on 30 patients and reported outcomes 12 months after surgery. Baser et al performed septorhinoplasty on 45 patients and reported a single outcome measurement at a time ranging from 6 to 30 months after surgery with an average of 12.89 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their analysis required pooling of data samples with different lengths of follow‐up and different intervals of reporting, prohibiting drawing definitive conclusions regarding the trend of NOSE scores longitudinally. For example, San Nicolo et al performed polylactic acid copolymer implants within the nasal wall for lateral cartilage support on 30 patients and reported outcomes 12 months after surgery. Baser et al performed septorhinoplasty on 45 patients and reported a single outcome measurement at a time ranging from 6 to 30 months after surgery with an average of 12.89 months.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ideal follow‐up duration after functional septorhinoplasty has not yet been determined. Previous literature utilizing NOSE scores report variable follow‐up, ranging from 1 month to 4 years …”
Section: Introductionmentioning
confidence: 99%
“…from Germany published the first clinical study of 30 patients in whom dynamic NVC was a major contributor to NAO symptoms. They showed that the bioabsorbable implant could be placed under local anesthesia in the physicians’ office or under general anesthesia in the operating room, and that it significantly improved NAO symptoms with a low retrieval rate and minimal cosmetic impact . A follow‐up study by the same authors showed that the effect of the implant was stable up to 24 months .…”
mentioning
confidence: 99%
“…Prospective, nonrandomized, single‐arm clinical studies have examined the safety and effectiveness of this device by comparing NAO symptoms before and after treatment. San Nicoló et al . from Germany published the first clinical study of 30 patients in whom dynamic NVC was a major contributor to NAO symptoms.…”
mentioning
confidence: 99%
“…Hence, the use of these aforementioned materials has been reserved as the last choice for implantation . Absorbable polymer implants such as polydioxanone (PDA), and polylactic acid (PLA) copolymers have become a compelling option for nasal graft applications as they may reduce the postoperative complications such as extrusions while continuing to provide structural support as the resorbed graft material is replaced with scar tissue.…”
Section: Introductionmentioning
confidence: 99%